QUANTITATIVE DETERMINATION OF THE CONTENT OF OMEGA-3 AND OMEGA-6 FATTY ACIDS IN THE COMPOSITION OF DRY MILK MIXTURES BY THE METHOD OF GAS CHROMOTOGRAPHY - Gulnoza Zinatullayevna Dzhakhangirova; Bekmurodova Sabina Kutlug kizi; Sodikov Samandar Ibrokhimjon ugli; Razzakov Sergey Sadritdinovich (Journals Park Publishing, 2022)
The aim of the study is to determine the quantitative composition of fatty acids in the composition of oils in dry milk porridges. Several methods have been explored for determining the composition of the extracted oil. By comparing the relevance and availability of methods, a gas chromatographic test method was chosen. In conclusion, all the results and data obtained are summarized.
Keywords: omega-3; omega-6; gas-liquid chromatography